Does Pluralism Matter for the Fulfillment of the Right to Education? Exploring New Indices - Wodon, Quentin (Taylor and Francis, 2021)
There is not a lot of support in the international community today for the role played by the private sector, including faith-based schools, towards achieving the fourth sustainable development goal (SDG), which calls for ensuring inclusive and equitable quality education. Yet, education pluralism is called for in the UN Universal Declaration of Human Rights. In a separate paper published in this journal, a measure of education pluralism was suggested to reflect this idea. In this paper, that measure is combined with data on educational outcomes to assess whether taking pluralism seriously may affect assessments of the fulfillment of the right to education.